2019
DOI: 10.2478/pomr-2019-0031
|View full text |Cite
|
Sign up to set email alerts
|

On Some Problems in Determining Tensile Parameters of Concrete Model from Size Effect Tests

Abstract: The paper presents results of numerical simulations of size effect phenomenon in concrete specimens. The behaviour of in-plane geometrically similar notched and unnotched beams under three-point bending is investigated. In total 18 beams are analysed. Concrete beams of four different sizes and five different notch to depth ratios are simulated. Two methods are applied to describe cracks. First, an elasto-plastic constitutive law with a Rankine criterion and an associated flow rule is defined. In order to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is easily observed that both elastic and post-peak softening responses match well with the experimental data for all cases considered. This is a huge improvement compared to the conventional nonlocal enhancement, discussed comprehensively by Gr egoire et al ( 2013); Havla´sek et al (2016); Marzec and Bobi nski (2019a) in the context of integral approach, and is thus not repeated here. A brief presentation with the conventional gradient enhancement was presented by Wosatko et al (2018), and also demonstrated briefly in third section where the same set of parameters cannot be used for the notched and unnotched beams considered.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…It is easily observed that both elastic and post-peak softening responses match well with the experimental data for all cases considered. This is a huge improvement compared to the conventional nonlocal enhancement, discussed comprehensively by Gr egoire et al ( 2013); Havla´sek et al (2016); Marzec and Bobi nski (2019a) in the context of integral approach, and is thus not repeated here. A brief presentation with the conventional gradient enhancement was presented by Wosatko et al (2018), and also demonstrated briefly in third section where the same set of parameters cannot be used for the notched and unnotched beams considered.…”
Section: Resultsmentioning
confidence: 94%
“…Since conventional nonlocal enhancements cannot describe the evolution and propagation of damage process zones correctly, they are inadequate in capturing both types of size effects. This limitation was reported extensively for the integral approach (Gr egoire et al, 2013;Havla´sek et al, 2016;Marzec and Bobi nski, 2019a), and briefly illustrated for the gradient approach in Wosatko et al (2018).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…deformation of a material body -the crux of this paper) in relation to its dimensions, date to the investigations of Leonardo da Vinci at the very beginning of XVI century [1,2]. Since that time both experimental techniques [3][4][5][6][7] and theoretical concepts [8][9][10][11][12][13] for SE analysis were considerably developed and moreover SE phenomena were utilised successfully in the modern industry [14][15][16][17][18]. The main message is that from the standpoint of mechanics, which constitutes the central point of presented considerations, one can say that each structure, due to the complexity of material over different scales of observation, reveals SE.…”
Section: Introductionmentioning
confidence: 99%